Avifaunal Diversity of Malguzari Lake at Zaliya near Amgaon in Gondia district (M.S.) India - Puri SD (International Journal of Life Sciences, 2015)
The Malguzari Lake is located at Zaliya having rich aquatic vegetation and harbors several kinds of birds. The present study deals with the avifaunal diversity of Malguzari Lake at Zaliya near Amgaon in Gondia district of Maharashtra. The survey was conducted twice in a month from October 2014 to May 2015 during the day time depending on the light conditions. The twenty seven species were recorded belonging to 08 different orders and 11 families during the study period. Out of 27 recorded species, 13 were residents, 10 were resident migrants and 04 were migrants. The abundance status also recorded, maximum species were sighted during the winter season followed by summer season.